Comparative Analysis and Factors Affecting The Competitiveness of Indonesian Cocoa Commodities In The German Market - Utama, Hardian Putra; Setiawina, Nyoman Djinar (Jurnal Manajemen, 2023)
Germany is one of Indonesia's cocoa export destinations because Germany is the largest importer of cocoa products in the European Union. This research purposed to analyze competitiveness and factors that affect the competitiveness of Indonesian cocoa commodity exports in the German market. This paper used secondary data which is got from legal sources with time series data from 2011-2022 and used Revealed Comparative Advantages (RCA) analysis to know the competitiveness (comparative) of a commodity and used multiple regression analysis with the Error Correction Models (ECM) approach to determine the effect of variables tested in this study. The results of RCA calculation of Indonesian cocoa on the German market show that the average RCA value of the cocoa commodity for the period 2011-2014 is more than one (RCA > 1), meaning that Indonesian cocoa commodity had a strong competitiveness in the German market, Indonesian cocoa bean commodity had a stronger competitiveness than its processed cocoa on that period. However, in the 2015-2022 period, the average value of the RCA of cocoa beans was 0.39, and the average value of processed cocoa RCA was 8.32, meaning that Indonesian processed cocoa commodities had stronger competitiveness than cocoa beans. The results of the ECM analysis showed that international cocoa price variables and Indonesian export duty policy have a positive and significant effect while Indonesian cocoa productivity and chocolate consumption per capita.